2019
DOI: 10.21608/ajnsa.2019.4970.1115
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the gas mixing ratio on some characteristics and reaction rate coefficients of Ar/N2 and He/N2 DC plasma

Abstract: The aim of this study is to analyze the relation between the reaction rate coefficients, hence the production of active species, and the gas mixing ratio in a comparative way between Ar/N 2 and He/N 2 gaseous mixtures. The Ar and He contributions ranged from 0 to 100 % at a total gas pressure of 0.4 Torr and a reduced electric field E/N of 610 Td. Langmuir probe is employed to measure electron temperature. The results showed that adding Ar to N 2 plasma reduced both the discharge operating voltage and the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the case of Ar in an H 2 plasma, Sode et al [49] show that T e decreases monotonically and they xvii attributed the observed decrease to the increasing eective ion mass with increasing Ar fraction. As described by El-Sayed et al [50], Ar can induce the dissociation of molecular nitrogen and increase the production of nitrogen atoms, however it has an insignicant eect on the nitrogen ionization mechanism. On the other hand, He addition enhances the production of, N + and N − atoms through ionization, ionization dissociation and dissociative reaction, however it has a decreasing eect on the dissociative recombination mechanism.…”
Section: He and Ar Eectmentioning
confidence: 97%
“…In the case of Ar in an H 2 plasma, Sode et al [49] show that T e decreases monotonically and they xvii attributed the observed decrease to the increasing eective ion mass with increasing Ar fraction. As described by El-Sayed et al [50], Ar can induce the dissociation of molecular nitrogen and increase the production of nitrogen atoms, however it has an insignicant eect on the nitrogen ionization mechanism. On the other hand, He addition enhances the production of, N + and N − atoms through ionization, ionization dissociation and dissociative reaction, however it has a decreasing eect on the dissociative recombination mechanism.…”
Section: He and Ar Eectmentioning
confidence: 97%